CRYPTOSPORIDIOSIS PARU DI HIV DAN AIDS - JS. Hutagalung; R. Heru Prasetyo; Erwin Astha Triyono (Indonesian Association of Clinical Pathologist and Medical laboratory, 2012)
Although the prevalence of intestinal cryptosporidiosis in Indonesian HIV and AIDS patients were high, however the prevalence of pulmonary cryptosporidiosis have not been previously reported. The objective of this study was to know the determination of the pulmonary cryptosporidiosis prevalence in HIV and AIDS patients with pulmonary symptom that was treated in Dr. Soetomo General Hospital Surabaya. The detection of Cryptosporidium in sputum samples used modified versien acid fast stain of Ziehl Neelsen technique. In this study was found that three (3) of the eight (8) sputum samples (37.5%) of ≥55 years old and CD4≤70 HIV and AIDS patients were Cryptosporidium positive. Based on this study the HIV and AIDS patients with pulmonary symptoms should be suspect having the possibility of pulmonary cryptosporidiosis beside suffered tuberculosis.